Mutation in the xpsD gene of Xanthomonas axonopodis pv. citri affects cellulose degradation and virulence - Baptista, Juliana Cristina (Sociedade Brasileira de Genética, 2010)
The Gram-negative bacterium Xanthomonas axonopodis pv. citri, the causal agent of citrus canker, is a major threat to the citrus industry worldwide. Although this is a leaf spot pathogen, it bears genes highly related to degradation of plant cell walls, which are typically found in plant pathogens that cause symptoms of tissue maceration. Little is known on Xac capacity to cause disease and hydrolyze cellulose. We investigated the contribution of various open reading frames on degradation of a cellulose compound by means of a global mutational assay to selectively screen for a defect in carboxymethyl cellulase (CMCase) secretion in X. axonopodis pv. citri. Screening on CMC agar revealed one mutant clone defective in extracellular glycanase activity, out of nearly 3,000 clones. The insertion was located in the xpsD gene, a component of the type II secretion system (T2SS) showing an influence in the ability of Xac to colonize tissues and hydrolyze cellulose. In summary, these data show for the first time, that X. axonopodis pv. citri is capable of hydrolyzing cellulose in a T2SS-dependent process. Furthermore, it was demonstrated that the ability to degrade cellulose contributes to the infection process as a whole.